Leadership and Implementation of Total Quality Management: A Case Study of Employee Performance Improvement in Hospitals - Rina Indah Hariyanti; Dyah Erny Herwindiati; Mahlia Muis (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to find out and analyze the influence of leadership on employee performance through the mediation of the implementation of Total Quality Management (TQM). The research design used is a survey research that takes samples from a population and uses questionnaires as a tool for collecting basic data. The research locations were carried out at Koja General Hospital, Sulianti Saroso Infectious Special Hospital, and TK II TNI AD M Ridwan Hospital. The number of population as well as the sample in this study is 240 people. To meet the assumptions and analysis models in this study, the Likert Scale was used. The analysis technique used in this study is path analysis using the Amos program. The results of the study show that leadership variables have a significant effect on the implementation of TQM, leadership has a significant effect on employee performance. Leadership has a significant effect on employee performance through the implementation of TQM.